Commentary by Juliet Cohen:: Ethical criteria when a (potential) perpetrator asks a human rights organization to defend their case based on the forensic documentation of alleged torture. How shall we proceed? - Cohen, Juliet (Torture Journal, 2020)
This is a response to the article debating what are the ethics of providing medico-legal reports for a victim of torture who may also be a perpetrator. There are important considerations to make, but in summary, we should treat all patients equally according to their healthcare needs, and leave the determination of guilt or innocence to others.